From local to global. New paths for publishing in Africa. - (:unkn) unknown (My University, 2016)
This paper focusses on the publishing sector in Africa and its recent developments. What are the major challenges, the difficulties but also the new opportunities faced by local publishers? Issues such as "print-languages" (Anderson) (including African ones), biblio-diversity and the use of new technologies are amongst the ones adressed here.
Keywords: African Research